Words and meanings lexical semantics across domains, languages, and cultures - Goddard, Cliff; Wierzbicka, Anna (Oxford Oxford University Press, 2014)
"In a series of cross-cultural investigations of word meaning, Cliff Goddard and Anna Wierzbicka examine key expressions from different domains of the lexicon - concrete, abstract, physical, sensory, emotional, and social. They focus on complex and culturally important words in a range of languages that includes English, Russian, Polish, French, Warlpiri and Malay."--Publishers website.
Words, Meaning, and Methodology -- Men, Women, and Children: The semantics of basic social categories -- Sweet, Hot, Hard, heavy, Rough, Sharp: Physical quality words in cross-linguistic perspective -- From Colour Words to Visual Semantics: English, Russian, Warlpiri -- Happiness and Human Values in Cross-cultural and Historical Perspective -- Pain Is it a Human Universal? The Perspective From Cross-linguistic Semantics -- Suggesting, Apologising, Complimenting: English speech act verbs -- A Stitch in Time and The Way of The Rice Plant: The semantics of proverbs in English and Malay -- The Meaning of Abstract Nouns: Locke, Bentham and Contemporary Semantics -- Broader Perspectives: Beyond lexical semantics.
Includes bibliographical references (pages 262-290) and index.
Keywords: Semantics